Peranan Visa Proteksi Dalam Kacamata Hukum Internasional (The Role Of Protection Visa In International Law) - Nur Arsy Widigusti; Nabila Annisa Ramadanti; Fazrina Putri Herdiansyah; Lutfiah Nurul Qothimah; Dewi Rahmawati Gustini (Peneliti.net, 2023)
Protection visas are an important instrument in providing international protection to individuals who face serious risks in their home countries. This journal aims to investigate the role and challenges associated with protection visas in providing such protection. This research uses normative juridical method. The specifications used are descriptive-analytical. Then the data used is secondary data. by collecting data from various sources, including media reports and related official sources. Through an in-depth analysis of the role and challenges of protection visas, it is hoped that this journal can provide valuable insights into efforts to protect individuals in need in the context of international law. This research contributes to broadening our understanding of international protection and explores the potential for developing a better protection visa system in the future. The results of the study show that the granting of a protection visa to Bima by Australia has caused controversy regarding immigration policy and violations of human rights